In vivo biodistribution analysis of [68Ga]Ga-NOTA-pamidronic acid and [68Ga]Ga-DOTA-pamidronic acid: insights into bone-targeting radiopharmaceuticals - Hassan, Hishar; Omar Samri, Nur Faqihah; Wan Kamal, Wan Hamirul Bahrin; Othman, Muhamad Faiz (Elsevier BV, 2025)
Radiolabeled bisphosphonates have shown the potential for targeted bone applications in both diagnostic imaging and therapy. In this study, we investigated the radiochemical properties and in vivo biodistribution of two novel radiopharmaceuticals; [68Ga]Ga-NOTA-pamidronic acid and [68Ga]Ga-DOTA-pamidronic acid, with the aim of determining their suitability for clinical applications. Radiolabeling was achieved with a high radiochemical purity (RCP) of over 95 % for both, with [68Ga]Ga-DOTA-pamidronic acid having a slightly higher RCP (99.48 %) compared to [68Ga]Ga-NOTA-pamidronic acid (97.48 %). This difference emphasises the superior affinity of DOTA for binding Ga3+ ions, which is likely due to its structural flexibility and enhanced coordination capabilities. The biodistribution studies were performed in healthy Swiss Webster mice. Both radiopharmaceuticals showed efficient renal clearance and minimal non-specific uptake in the major organs. The kidneys and bladder showed the highest uptake, indicating renal excretion, with [68Ga]Ga-DOTA-pamidronic acid showing significantly higher uptake in the bladder. However, bone uptake remained relatively low for both radiopharmaceuticals, with [68Ga]Ga-NOTA-pamidronic acid showing higher uptake (1.33 %ID/g) compared to [68Ga]Ga-DOTA-pamidronic acid (0.26 %ID/g). This may be attributed to rapid excretion and the possible changes in bisphosphonate binding properties due to chelation. Free 68Ga showed extensive non-specific uptake, highlighting the advantages of chelated radiotracers in minimising off-target distribution. While [68Ga]Ga-NOTA-pamidronic acid and [68Ga]Ga-DOTA-pamidronic acid showed promising renal clearance and minimal non-specific uptake, their bone affinity remains suboptimal. These results emphasise the need for further structural modifications to improve binding to hydroxyapatite and thus provide the basis for the development of 68Ga-based radiopharmaceuticals with improved bone-targeting capabilities.